Использование визуализации при разработке и проверке регламентов (рабочих инструкций) - Гуца, О. Н.; Довгопол, Н. В. (ХНУРЭ, 2015)
Features of human perception and information processing do not allow complete coverage and properly assess the Procedures (Algorithms) as text on the Logical Coherence and Consistency, so it is necessary to include the step of displaying them in a Logic Scheme in the language of BPMN in the development or testing Regulation.
Keywords: использование визуализации; проверка регламентов